Risk and uncertainty in the art world - Dempster, Anna M. (Bloomsbury, 2014)
This edited book offers the first complete overview of risk in the art market by bringing together contributions from a wide range of international thought-leaders on the topic - both practitioners and leading scholars who investigate the specific types of uncertainty that exist in the art market as well as the dominant models used to manage the risks. An essential read for both art world practitioners, as well as scholars and students, Risk and Uncertainty in the Art Market elucidates the dynamics and unique qualities of the art market as well as developing insights relevant to other sectors,
Keywords: Art as an investment.; Risk assessment -- Methodology.; Art -- Marketing.; Art comme valeur de placement.; Évaluation du risque -- Méthodologie.; Art -- Commercialisation.; art market.; BUSINESS & ECONOMICS -- Industries -- General.; Art as an investment; Art -- Marketing; Risk assessment -- Methodology; Electronic book.